Increased endogenous dopamine prevents myopia in mice. (April 2020) - Landis, E.G.; Chrenek, M.A.; Chakraborty, R.; Strickland, R.; Bergen, M.; Yang, V.; Iuvone, P.M.; Pardue, M.T.
Abstract: Experimental evidence suggests that dopamine (DA) modulates refractive eye growth. We evaluated whether increasing endogenous DA activity using pharmacological or genetic approaches decreased myopia susceptibility in mice. First, we assessed the effects of systemic L-3, 4-dihydroxyphenylalanine (L-DOPA) injections on form deprivation myopia (FDM) in C57BL/6 J (WT C57 ) mice. WT C57 mice received daily systemic injections of L-DOPA (n = 11), L-DOPA + ascorbic acid (AA, n = 22), AA (n = 20), or Saline (n = 16). Second, we tested transgenic mice with increased or decreased expression of vesicular monoamine transporter 2 (VMAT2 HI, n = 22; WT HI, n = 18; VMAT2 LO, n = 18; or WT LO, n = 9) under normal and form deprivation conditions. VMAT2 packages DA into vesicles, affecting DA release. At post-natal day 28 (P28), monocular FD was induced in each genotype. Weekly measurements of refractive error, corneal curvature, and ocular biometry were performed until P42 or P49. WT C57 mice exposed to FD developed a significant myopic shift (treated-contralateral eye) in AA (−3.27 ± 0.73D) or saline (−3.71 ± 0.80D) treated groups that was significantly attenuated by L-DOPA (−0.73 ± 0.90D, p = 0.0002) or L-DOPA + AA (−0.11 ± 0.46D, p = 0.0103). The VMAT2 LO mice, with under-expression of VMAT2, were most susceptible to FDM. VMAT2 LO mice developed significant myopic shifts to FD after one week compared to VMAT2 HI and WT mice (VMAT2 LO : −5.48 ± 0.54D; VMAT2 HI : −0.52 ± 0.92D, p < 0.05; WT: −2.13 ± 0.78D, p < 0.05; ungoggled control: −0.22 ± 0.24D, p < 0.001). These results indicate that endogenously increasing DA synthesis and release by genetic and pharmacological methods prevents FDM in mice. Highlights: Systemic L-DOPA administration prevents form-deprivation myopia in mice. The dopamine packaging protein VMAT2 may affect early form-deprivation myopia. Endogenously increased dopamine activity prevents form-deprivation myopia in mice.